Institutional Support of the Renewable Energy Industry in Ukraine - Nataliia, Riazanova; ., . (International Journal of Engineering and Technology, 2018)
The article considers the institutional aspect of the renewable power industry development in Ukraine as a complex of formal and informal institutions, certain rules that actively influence the development and implementation of technologies. The development of the renewable energy industry through institutional transformations should be at the highest hierarchical level. The factors hindering the development of renewable energy sources (RES) are highlighted and systematized. In order to eliminate these factors, significant institutional changes that can not be carried out outside targeted state policies are needed, including financial support for the industry, the elimination of regulatory barriers, and the formation of demand for equipment by the strengthening of environmental norms and other tools for stimulating the development of renewable energy power industry and coordination of energy market participants. Key segments that influence the development of RES are formulated. Certain institutional transformations are needed for qualitative development of renewable energy power industry in Ukraine. Necessary institutional changes in energy supply, and now the state needs to systematize and harmonize the RES-policy. Institutional transformations are reduced to the problems of the development of renewable energy power industry in Ukraine, the ways of their solution are determined. The actions of economic entities in the economic space with the distribution (regulation) of each of them for the stable functioning of the system, which are the basis of the institutional relationship of renewable energy sources in Ukraine for the purpose of energy saving, are presented.Â Â